Population, Education and Income Inequality - Parcero, Osiris Jorge (Journal of Income Distribution®, 2021)
In non-democracies, a large population size and density lead to more redistributive policies and lower income inequality. This is the result of the interconnection of two intermediate hypotheses. First, in non-democracies a larger population size and density increase the chance of a revolution attempt to overthrow the governing elites. Second, this revolution threat prompts the elites to better re-distribute the country’s income in an attempt to fend off this threat. This paper suggests and empirically tests that wider spread primary and, to a lesser extent, secondary education is one of the channels through which the elites achieve this better distribution.